2020
DOI: 10.1177/0033688220935478
|View full text |Cite
|
Sign up to set email alerts
|

Representations of the English as a Lingua Franca Framework: Identifying ELF-aware Activities in Portuguese and Turkish Coursebooks

Abstract: The international role of English has made it the most taught foreign language in the world. As a result, standard native varieties have thrived as models within the field of English language teaching, particularly Standard British English and Standard American English, and alongside, the cultures associated with them. Although the majority of English language learners are part of Kachru’s Expanding Circle, teaching materials have continued to focus on native speaker models, neglecting many of the times other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…In her analysis of these school practices, Cavalheiro (2020) highlights the ideas of identity, emergence, and negotiation associated to elf. Guerra et al (2020) reports a comparative study about English language teaching materials developed by researchers from Portugal, such as Guerra himself, Pereira, and Cavalheiro, and from Turkey, such as Kurt, Oztekin, Sonmez-Candan, and Bayyurt. They aimed at analyzing if different uses of English in international communication are present in materials from these two countries.…”
Section: Interrupting Coloniality: Voices From Other Europesmentioning
confidence: 99%
“…In her analysis of these school practices, Cavalheiro (2020) highlights the ideas of identity, emergence, and negotiation associated to elf. Guerra et al (2020) reports a comparative study about English language teaching materials developed by researchers from Portugal, such as Guerra himself, Pereira, and Cavalheiro, and from Turkey, such as Kurt, Oztekin, Sonmez-Candan, and Bayyurt. They aimed at analyzing if different uses of English in international communication are present in materials from these two countries.…”
Section: Interrupting Coloniality: Voices From Other Europesmentioning
confidence: 99%
“…Consequently, they have largely neglected 'to acknowledge the increased use of English among NNSs [non-native speakers] of English' (Matsuda, 2012, p. 171), hence overlooking the plurality learners encounter outside the classroom. Research has also indicated that the role of ELF-as the most often used means in international and intercultural exchanges-has been largely underrepresented in textbooks and web-based teaching materials (Matsuda 2012;Vettorel and Lopriore 2013;Guerra et al 2020), as well as in ELF-aware teaching materials (Seidlhofer 2011). In order to bridge this gap, teachers may create their own materials, by resorting to authentic resources (e.g., television shows, movies, YouTube videos, newspapers/magazines) which reflect the current global use of English in which native and non-native speakers are represented in terms of different varieties and cultures (e.g., Guerra and Cavalheiro 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Mencionamos aqui alguns deles a fim de compreender que entendimentos de ILF embasam esses trabalhos e que temas são abordados nessas pesquisas. Cavalheiro (2020), pesquisadora portuguesa sobre o tema, define ILF como o inglês "falado em situações com combinações amplamente variáveis de participantes, incluindo falantes de primeiras línguas com diferentes variantes" 57 (MAURANEN, 2018, p. 8 apud CAVALHEIRO, 2020. Assim como Siqueira (2015Siqueira ( , 2018) e Gimenez, Calvo e El Kadri (2015,2018), que comentaremos adiante, Cavalheiro (2020) também articula ILF à possibilidade de promover trocas e diálogos interculturais e enxerga a sala de aula de língua inglesa como espaço de integração de estudantes migrantes.…”
Section: Vozes De 'Outras Europas'unclassified
“…Em Guerra et al (2020), um estudo comparativo sobre materiais didáticos para o ensino de língua inglesa é conduzido por pesquisadores de Portugal, como Guerra, Pereira e…”
Section: Vozes De 'Outras Europas'unclassified
See 1 more Smart Citation